Rituximab plus gemcitabine and oxaliplatin (R-GemOx) in refractory/relapsed diffuse large B-cell lymphoma: a real-life study in patients ineligible for autologous stem-cell transplantation. Issue 9 (29th July 2021) - Cazelles, Clarisse; Belhadj, Karim; Vellemans, Hélène; Camus, Vincent; Poullot, Elsa; Gaulard, Philippe; Veresezan, Liana; Itti, Emmanuel; Becker, Stéphanie; Carvalho, Muriel; Dupuis, Jehan; Le Bras, Fabien; et al.
Abstract: There is no established standard treatment for relapsed/refractory (R/R) diffuse large B-cell lymphoma (DLBCL) in patients who are not eligible to receive an intensive treatment. The combination of rituximab gemcitabine and oxaliplatin (R-GemOx) is widely used in this population but data are scarce. We retrospectively collected the data of 196 patients with R/R DLBCL treated with R-GemOx in two French centers over a period of 15 years. The median age of the population was 72 years (range, 24–89), 63% of the patients had an international prognostic index of 3 or higher and 57% were refractory to the last treatment. At the end of R-GemOx treatment, 33% of the patients obtained a complete response. The median progression-free survival (PFS) of the population was 5 months and the median overall survival (OS) was 10 months. Several factors were predictors of unfavorable survival: age over 75 years, international prognostic index of 2 or higher, refractory disease and de novo DLBCL. The median PFS and OS of the patients who obtained a complete response were 22 months and 40 months, respectively. The most significant toxicities were grade 3–4 hematological toxicities (31% of patients). Given its efficacy and tolerability, R-GemOx can be used in patients ineligible for intensive treatment and serve as a basis for new regimen combinations.